How do supreme audit institutions manage their autonomy and impact? A comparative analysis. Issue 2 (1st February 2019) - Pierre, Jon; de Fine Licht, Jenny
ABSTRACT: Supreme audit institutions (SAIs) are gradually becoming important agents of public management reform; a development raising issues of autonomy and potential capture by auditees as well as by the political system. Drawing on exploratory case studies of the rules and strategies of four high-performing SAIs – those of Australia, New Zealand, Norway and Sweden – the article shows that SAIs have different approaches to the balance between autonomy and impact. These results imply that there is not only one way of organizing an efficient and autonomous SAI, but that different positions can prove viable.